Unique Presentation of Septic Cavernous Sinus Thrombosis and Pulmonary Embolism in the Setting of Reusable Face Covering. (15th April 2022) - Barranco-Trabi, Javier; Scott, Jazmin C.; Fryer, Jacob M.; Byrne, Matthew; Smith, Adam; Song, Kaoru H.; Tagawa, Chelsea W.; Chi, Sharon; Ngauy, Viseth
Abstract : Identified in December 2019, SARS-CoV-2 quickly spread worldwide with a resultant increase in global morbidity, mortality, and economic disruption on a scale not seen since the 1918 Spanish flu. Health officials recommended universal masking to further reduce human-to-human spread of SARS-CoV-2. The state of Hawaii and the Department of Defense (DOD) adopted strict mask policies early in the pandemic and is shown to be effective at reducing transmission. We report a case of Staphylococcus aureus bacteremia in an immunocompetent 21-year-old man attributed to local skin irritation with resultant infection in the setting of continuous reuse of a mask that resulted in bilateral cavernous venous thrombosis and septic pulmonary embolism.